Tantangan Pendidikan Islam di Indonesia - Sukari, Sukari; Hartanto, Rudy; Priyanto, Catur (TSAQOFAH, 2026)
Islamic education plays a crucial role in shaping the character and quality of future generations in Indonesia, yet it currently faces multiple challenges arising from globalization, socio-cultural change, and technological advancement. This article aimed to discuss the challenges confronting Islamic education in Indonesia and the efforts that can be undertaken to address them, using a library research method and a descriptive approach. The review shows that the main challenges include the influence of globalization on students’ values and behaviour, limitations in the quality of human resources among educators, the limited relevance of parts of the curriculum to contemporary needs, the demands of learning digitalization, and ongoing issues surrounding the public image of Islamic education and the urgency of strengthening religious moderation. In response, it is necessary to enhance educator quality through the development of professional and pedagogical competence, to design curricula that are aligned with global dynamics and learners’ needs, to utilize technology wisely and purposefully within the learning process, and to reinforce values of religious moderation so that Islamic education remains relevant, inclusive, and of high quality in addressing the challenges of the times.